From Expectancy to Acceptance: The Impact of Performance and Effort Expectations on Mobile Commerce Intentions - Barry, Moussa; Haque, AKM Ahasanul; Jan, Muhammad Tahir (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2024)
Over the past few decades, there has been a significant advancement in the development of mobile commerce. This study examines the effect of performance expectancy, effort expectancy, and perceived trust on the acceptance of mobile commerce through intention. Convenience sampling was employed whereby 385 survey questionnaires were distributed to consumers residing in Malaysia's Klang Valley area who possess smartphones and engage in mobile commerce transactions. The study's hypotheses were determined using a two-phase structural equation modeling procedure. The results indicated that perceived trust, performance expectancy, and effort expectancy significantly impact the intention to utilize mobile commerce. Moreover, the acceptance of mobile commerce is significantlyimpacted by the intention of utilizing mobile commerce. The results also showed that perceived trust indirectly impacted the acceptance of mobile commerce through intention. However, these insights benefit mobile commerce providers and businesses seeking to improve the acceptance of mobile commerce transactions in Malaysia